End User Development: Survey of an Emerging Field for Empowering People. (10th June 2013) - Paternò, Fabio
Abstract : The purpose of this paper is to introduce the motivations behind end user development, discuss its basic concepts and roots, and review the current state of art. Various approaches are discussed and classified in terms of their main features and the technologies and platforms for which they have been developed. Lastly, the paper provides an indication of interesting possibilities for further evolution.